Feeding quality assessment of fresh maize stover by means of near-infrared spectroscopy with a new sample presentation unit - Montes, J.M.; Mirdita, V.; Prasad, K.; Blümmel, Michael; Melchinger, A.E. (Wiley, 2008)
Stover quality traits are important in breeding programmes of maize cultivars. However, conventional procedures for evaluation of stover quality are expensive and thus limit the full exploitation of the available genetic variability. Our objective was to assess the potential of near-infrared spectroscopy (NIRS) with a new sample presentation unit to determine feeding quality of maize stover. The plant material comprised maize inbreds and hybrids. The sample presentation unit was equipped with a near-infrared diode-array spectrometer. Coefficient of determination in cross-validation ranged between 0.77 and 0.94 for contents of dry matter, nitrogen, neutral detergent fibre and in vitro fermentability expressed as gas volume after 24h incubation time, but it was lower for ash content. It was concluded that NIRS with the new sample presentation unit was less accurate than laboratory NIRS to predict the standard reference methods. However, the new sample presentation unit might be used as a fast and efficient technique to perform large screenings of maize stover accessions in breeding programmes.